MOTIVASI KEAKTIFAN MAHASISWA DALAM MENGIKUTI KAJIAN ISLAM DI MASJID ARFA’UNNAS UNIVERSITAS RIAU - Hafiz, Muhammad; ', Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at the University of Riau - Pekanbaru. This study aims to determine the motivation of Riau University students in following Islamic studies at the Arfa'unnas Mosque, University of Riau. To find out the driving factors and impact of Riau University students in following Islamic studies at the Arfa'unnas Mosque at UNRI on their academic activities. This study was entitled "Motivation of Student Activity in Following Islamic Studies at the Arfa'unnas Mosque of the University of Riau (Study on Riau University Students). This study uses a qualitative approach with Purposive techniques. Subjects taken were Riau University students totaling 5 people with different generations starting from 2014-2016. Data analysis method used is qualitative data analysis by analyzing the questions posed to the research subject according to the data obtained and presented in a systematic and scientific sentence form. The results of the research in general have been conducted by researchers. According to researchers the motivation of University of Riau students to follow Islamic studies at the Arfa'unnas Mosque UNRI was due to several motivating factors, namely in the form of motivation from within and also motivation from outside the students. Motivation from within is the need for students to gain knowledge of their religion, then motivation from outside, among others, is the location of study that is on campus, favorite religious teachers, and peers. Then the impact that arises from the study on student academic activities is something positive, where students become better and increase their enthusiasm in undergoing lectures. Keywords: Motivation, Student, Islamic Studies, Universitas Riau